2017
DOI: 10.1186/s12711-017-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous fitting of genomic-BLUP and Bayes-C components in a genomic prediction model

Abstract: BackgroundThe rapid adoption of genomic selection is due to two key factors: availability of both high-throughput dense genotyping and statistical methods to estimate and predict breeding values. The development of such methods is still ongoing and, so far, there is no consensus on the best approach. Currently, the linear and non-linear methods for genomic prediction (GP) are treated as distinct approaches. The aim of this study was to evaluate the implementation of an iterative method (called GBC) that incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Our study demonstrated that ST-BayesCπ had better predictive ability than ST-GBLUP, with higher accuracy across all traits. These results are consistent with previous studies, suggesting Bayesian methods outperform GBLUP methods due to the assumption of different variances of SNP effects [2,16,27,40]. However, some studies based on real data suggested that the accuracies of GBLUP were similar to Bayesian methods [15,27,[40][41][42][43].…”
Section: Predictive Ability For Single Trait With Gblup and Bayescπsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study demonstrated that ST-BayesCπ had better predictive ability than ST-GBLUP, with higher accuracy across all traits. These results are consistent with previous studies, suggesting Bayesian methods outperform GBLUP methods due to the assumption of different variances of SNP effects [2,16,27,40]. However, some studies based on real data suggested that the accuracies of GBLUP were similar to Bayesian methods [15,27,[40][41][42][43].…”
Section: Predictive Ability For Single Trait With Gblup and Bayescπsupporting
confidence: 91%
“…These results are consistent with previous studies, suggesting Bayesian methods outperform GBLUP methods due to the assumption of different variances of SNP effects [2,16,27,40]. However, some studies based on real data suggested that the accuracies of GBLUP were similar to Bayesian methods [15,27,[40][41][42][43]. Additionally, research has suggested that the superiority of GBLUP over Bayesian methods was due to the genetic architecture of the studied trait [44].…”
Section: Predictive Ability For Single Trait With Gblup and Bayescπsupporting
confidence: 90%
“…Bayesian methods that are implemented using MCMC algorithms are time-consuming and computationally demanding when they handle large number of SNPs. Therefore, several iterative (non-MCMC-based Bayesian) methods such as VanRaden's non-linear A/B (VanRaden, 2008), fastBayesB (Meuwissen et al ., 2009), MixP (Yu and Meuwissen, 2011) or emBayesR (Habier et al ., 2007) were developed to overcome the computational demands (Iheshiulor et al ., 2017). The aforementioned methods are computationally fast, and they result in prediction accuracies similar to those of the MCMC-based methods.…”
Section: Traditional Animal Breeding Prediction Methodsmentioning
confidence: 99%
“…Models that simultaneously fit a GBLUP and a BayesC term have been used before in the literature, e.g. [9,32,33], and have been shown to yield high prediction accuracy. Our current implementation of this model is specifically directed at the use of sequence data.…”
Section: Discussionmentioning
confidence: 99%